Redox-Responsive Repressor Rex Modulates Alcohol Production and Oxidative Stress Tolerance in Clostridium acetobutylicum - Zhang, Lei (J Bacteriol, 2014)
Rex, a transcriptional repressor that modulates its DNA-binding activity in response to NADH/NAD(+) ratio, has recently been found to play a role in the solventogenic shift of Clostridium acetobutylicum. Here, we combined a comparative genomic reconstruction of Rex regulons in 11 diverse clostridial species with detailed experimental characterization of Rex-mediated regulation in C. acetobutylicum. The reconstructed Rex regulons in clostridia included the genes involved in fermentation, hydrogen production, the tricarboxylic acid cycle, NAD biosynthesis, nitrate and sulfite reduction, and CO(2)/CO fixation. The predicted Rex-binding sites in the genomes of Clostridium spp. were verified by in vitro binding assays with purified Rex protein. Novel members of the C. acetobutylicum Rex regulon were identified and experimentally validated by comparing the transcript levels between the wild-type and rex-inactivated mutant strains. Furthermore, the effects of exposure to methyl viologen or H(2)O(2) on intracellular NADH and NAD(+) concentrations, expression of Rex regulon genes, and physiology of the wild type and rex-inactivated mutant were comparatively analyzed. Our results indicate that Rex responds to NADH/NAD(+) ratio in vivo to regulate gene expression and modulates fermentation product formation and oxidative stress tolerance in C. acetobutylicum. It is suggested that Rex plays an important role in maintaining NADH/NAD(+) homeostasis in clostridia.